2017
DOI: 10.3390/molecules22020308
|View full text |Cite
|
Sign up to set email alerts
|

Natural Products as Chemopreventive Agents by Potential Inhibition of the Kinase Domain in ErbB Receptors

Abstract: Small molecules found in natural products provide therapeutic benefits due to their pharmacological or biological activity, which may increase or decrease the expression of human epidermal growth factor receptor (HER), a promising target in the modification of signaling cascades involved in excessive cellular growth. In this study, in silico molecular protein-ligand docking protocols were performed with AutoDock Vina in order to evaluate the interaction of 800 natural compounds (NPs) from the NatProd Collectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…The various studies have proved that hesperidin has a capacity to induce cancer cell death including breast, lung, colon, liver, and gastric cancers [ 6 , 19 ]. Also, a study showed that the hesperidin significantly inhibits the colony formation of MCF7 cells [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The various studies have proved that hesperidin has a capacity to induce cancer cell death including breast, lung, colon, liver, and gastric cancers [ 6 , 19 ]. Also, a study showed that the hesperidin significantly inhibits the colony formation of MCF7 cells [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…A study has shown that the expression of this receptor significantly increases in breast cancer up to 80% of cells [ 5 ]. Also, the human epidermal growth factor receptor (HER) generates a cascade of responses able to advance the formation and progression of breast cancer [ 6 ]. Therefore, the activation of HER receptors leads to modification in the behavior of normal cells through the final signals for cellular proliferation, anti-apoptosis, angiogenesis, and metastasis [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Baicalein, a compound found in all three samples, is significant because it has powerful antioxidant properties that can induce programmed cell death in breast and carcinogenic ovarian cells ( 32 ). Podototarin is a bisditerpenoid that can reduce rapid growth and proliferation ( 33 ). The VER sample had a higher content of Podototarin than that in the LA and TX samples.…”
Section: Resultsmentioning
confidence: 99%